1997
DOI: 10.1074/jbc.272.45.28660
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Meizothrombin and Meizothrombin(desF1) by Heparin Cofactor II

Abstract: Meizothrombin and meizothrombin(desF1) are intermediates formed during the conversion of prothrombin to thrombin by factor Xa, factor Va, phospholipids, and Ca 2؉ (prothrombinase). These intermediates are active toward synthetic peptide substrates but have limited ability to interact with platelets or macromolecular substrates such as fibrinogen. Meizothrombin and meizothrombin(desF1) activate protein C, however, and may exert primarily an anticoagulant effect. In this study, we investigated the inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Previous structural (39) and functional (40,41) data indicate that F2 binds exosite 2. Consequently, exosite 2 should only be accessible on thrombin and pre2, derivatives lacking F2.…”
Section: Competitive Binding Of Exosite 1 Ligands To Thrombin Andmentioning
confidence: 99%
“…Previous structural (39) and functional (40,41) data indicate that F2 binds exosite 2. Consequently, exosite 2 should only be accessible on thrombin and pre2, derivatives lacking F2.…”
Section: Competitive Binding Of Exosite 1 Ligands To Thrombin Andmentioning
confidence: 99%
“…Removal of F2 from the proteinase domain thus does not affect the affinity of exosite I for the specific peptide ligand. Previous studies indicated no detectable binding of thrombomodulin to exosite I on human Pre 2 (31), whereas fluorescein-labeled hirudin [53][54][55][56][57][58][59][60][61][62][63][64] (hirugen) bound with the same high affinity to bovine Pre 2 as to bovine thrombin (32). The source of this difference is not known but may be due to intrinsic differences in the affinities for human and bovine Pro species (26).…”
Section: Discussionmentioning
confidence: 99%
“…Both MzT and MzT(-F1), however, bind thrombomodulin with affinity comparable to thrombin and exhibit comparable activity in protein C activation (53,55), which are also exosite I-dependent processes. Similarly, MzT and MzT(-F1) react with the exosite I-dependent inhibitors, hirudin (55) and heparin cofactor II (56), and MzT(-F1) binds an exosite I-specific antibody (31). The low activity of MzT and MzT(-F1) in factor V activation may reflect the participation of exosite II, which is inaccessible on MzT and MzT(-F1), in addition to exosite I (19 -21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of thrombin exosite-1 has been partially characterized using dysthrombin Quick 1 (R62C) (50), ␥ T -and ⑀-thrombins (27,30,51), exosite-1 mutants R68E and R70E (5), and 10 basic exosite-1 residues changed to Gln (38). In the current study, we measured the inhibition of 22 different Ala-scanned exosite-1 thrombin mutants.…”
Section: Use Of Ala-scanned Mutants For Thrombin Structure-activitymentioning
confidence: 99%